Western Diet Decreases the Liver Mitochondrial Oxidative Flux of Succinate: Insight from a Murine NAFLD Model - Staňková, Pavla; Kučera, Otto; Peterová, Eva; Elkalaf, Moustafa; Rychtrmoc, David; Melek, Jan; Podhola, Miroslav; Zubáňová, Veronika; Červinková, Zuzana (International journal of molecular sciences, 2021)
Mitochondria play an essential role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Previously, we found that succinate-activated respiration was the most affected mitochondrial parameter in mice with mild NAFLD. In this study, we focused on the role of succinate dehydrogenase (SDH) in NAFLD pathogenesis. To induce the progression of NAFLD to nonalcoholic steatohepatitis (NASH), C57BL/6J mice were fed a Western-style diet (WD) or control diet for 30 weeks. NAFLD severity was evaluated histologically and the expression of selected proteins and genes was assessed. Mitochondrial respiration was measured by high-resolution respirometry. Liver redox status was assessed using glutathione, malondialdehyde, and mitochondrial production of reactive oxygen species (ROS). Metabolomic analysis was performed by GC/MS. WD consumption for 30 weeks led to reduced succinate-activated respiration. We also observed decreased SDH activity, decreased expression of the SDH activator sirtuin 3, decreased gene expression of SDH subunits, and increased levels of hepatic succinate, an important signaling molecule. Succinate receptor 1 (SUCNR1) gene and protein expression were reduced in the livers of WD-fed mice. We did not observe signs of oxidative damage compared to the control group. The changes observed in WD-fed mice appear to be adaptive to prevent mitochondrial respiratory chain overload and massive ROS production.
Keywords: Mitochondria, Liver; jaterní mitochondrie; Animals; apoptóza; Succinate Dehydrogenase; biologické markery; oxidační stres; kyselina jantarová; Diet, Western; Biomarkers; nealkoholová steatóza jater; Apoptosis; buněčné dýchání; Fibrosis; Succinic Acid; Oxidative Stress; Mice; Metabolomics; myši; metabolomika; oxidace-redukce; metabolom; modely nemocí na zvířatech; Oxidation-Reduction; Disease Susceptibility; Cell Respiration; Disease Models, Animal; Non-alcoholic Fatty Liver Disease; Metabolome; zvířata; fibróza; západní dieta; sukcinátdehydrogenasa; náchylnost k nemoci